Perceraian Di Luar Pengadilan Ditinjau Dari Perspektif Janda: Studi Kasus Di Desa Tanjung Medan - Kumala, Wati; Syahputra, Akmaluddin; Firmansyah, Heri (Jayapangus Press, 2025)
The practice of divorce outside of religious courts in Tanjung Medan Village raises a number of issues, particularly regarding the fulfillment of children's rights and the division of joint property. The purpose is to analyze the incompatibility of this practice with Islamic law and to provide recommendations for solutions to address these issues. The research method is qualitative research using a normative empirical approach. Research findings Through a case study in Tanjung Medan Village, it was found that divorce outside religious courts often results in legal uncertainty, unfair distribution of assets, and difficulties in enforcing children's rights. This study aims to analyze to what extent such practices contradict the principles of justice in Islamic law. A thorough analysis of these findings shows that such practices are difficult to justify from an Islamic legal perspective. Re-examines the legal status of divorce outside of court, which is fundamentally permissible under fiqh, by reviewing the principles of fiqh to determine whether its legal status can change to haram, makruh, or remain permissible. The research findings are expected to serve as input for the public, religious leaders, and policymakers in achieving justice for all parties involved in the divorce process.